2000
DOI: 10.1111/j.1741-3737.2000.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on Domestic Violence in the 1990s: Making Distinctions

Abstract: ࡗResearch on Domestic Violence in the 1990s: Making DistinctionsThis review of the family literature on domestic violence suggests that two broad themes of the 1990s provide the most promising directions for the future. The first is the importance of distinctions among types or contexts of violence. Some distinctions are central to the theoretical and practical understanding of the nature of partner violence, others provide important contexts for developing more sensitive and comprehensive theories, and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
801
6
38

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 900 publications
(872 citation statements)
references
References 117 publications
(119 reference statements)
27
801
6
38
Order By: Relevance
“…41,42 Several studies have reported that men screened in the ED for IPV had similar rates of victimization by an intimate partner as women. 43,44 These studies and our own screening results might be documenting a high rate of low-level, bidirectional emotional or physical violence 45 and do not make a clear distinction between a victim or a perpetrator. One trauma unit study linked the names of men presenting to an ED with injuries inflicted by their female partner to police department records and found that half of these men had prior arrests for domestic violence perpetration.…”
Section: Discussionmentioning
confidence: 67%
“…41,42 Several studies have reported that men screened in the ED for IPV had similar rates of victimization by an intimate partner as women. 43,44 These studies and our own screening results might be documenting a high rate of low-level, bidirectional emotional or physical violence 45 and do not make a clear distinction between a victim or a perpetrator. One trauma unit study linked the names of men presenting to an ED with injuries inflicted by their female partner to police department records and found that half of these men had prior arrests for domestic violence perpetration.…”
Section: Discussionmentioning
confidence: 67%
“…We have argued, however, that both the conceptual and clinical utility of typological approaches seem quite limited. To date, presentations in the field of domestic violence generally emphasize only the value of the typological approach (e.g., Johnson & Ferraro, 2000) without properly addressing the issues addressed above. The batterer typology approach fails to embrace the increasing body of work supporting dyadic models and the influences of time, and it has yet to be converted into more targeted clinical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Porém é importante destacar que de maneira geral a mulher não perpetra agressões contra o parceiro na mesma intensidade e severidade que é cometida contra ela pelo parceiro homem 28 . Alguns estudos mostraram que as mulheres seriam mais prováveis a usar a agressão física do que os homens 29,30 , que tenderiam a usar armas e outros objetos como formas de agressão que não precisam da força física, além do uso da violência psicológica 31 que é um tipo de violência predominantemente cometida por mulheres contra seus parceiros.…”
Section: Discussionunclassified